Association Between Myasthenia Gravis and Memory: A Systematic Review and Meta-Analysis - Zhou, Xiaoling; Zhou, Yifei; Hua, Jianian; Xue, Qun (Frontiers in Neurology, 2021)
Objective: The studies have produced contradictory results regarding the association between myasthenia gravis (MG) and cognitive function, especially for the cognitive domains of memory. This meta-analysis was dedicated to exploring the association between MG and memory, which was represented by the immediate recall and delayed recall. Methods: Using the random effects models, this study analyzed memory in MG based on data from the studies retrieved from four electronic databases from inception to February 2021. Disease severity was graded according to the Myasthenia Gravis Foundation of America (MGFA) classification. We defined ocular myasthenia gravis (OMG) (MGFA Grade I) as Class I, mild, and moderate generalized myasthenia gravis (GMG) (MGFA Grade IIa, IIb, IIIa, and IIIb) as Class II. Results: In total, eight studies of 274 patients and 211 healthy controls were included. The significant associations were found between MG and memory. Compared with the healthy control group, the patients with MG performed significantly worse in the terms of immediate recall [standardized mean difference (SMD) = −0.65, 95% CI = −0.97 to −0.33, P < 0.001, I2 = 64.1%] and delayed recall (SMD = −0.49, 95% CI = −0.88 to −0.1, P < 0.05, I2 = 76.3%). Compared with the patients with Class I MG, those with Class II MG did not have significantly different scores in immediate recall (SMD = −0.07, 95% CI = −0.35 to 0.21, P = 0.614, I2 = 0%) and delayed recall (SMD = 0.63, 95% CI = −0.29 to 1.55, P = 0.178, I2 = 87.9%). Conclusion: The patients with MG showed lower memory performance, such as both immediate and delayed recall ability. There was no association between the severity of MG and memory. Future studies should address whether these associations are casual and modifiable.